Studi perbandingan penggunaan bahan bakar gas dan bahan bakar minyak pada mesin katinting - Levandri Alski Lumi; Fransisco P.T. Pangalila; Revols D. CH. Pamikiran; Kawilarang W.A. Masengi; Lefrand Manoppo; Heffry V. Dien (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2023)
Fuel is an important energy in fishing operations. Fuel is very influential on operational costs. One of the ways that fishermen can make a profit is by reducing the operational costs of fishing. Fuel consumption was calculated at least the amount of fuel used by the katinting engine at three different RPMs, using a ratio of pertalite type fuel oil and 3 kg LPG gas fuel with an engine operating time of 15 minutes. The average pertalite consumption at low RPM is Rp.1,784.25, while the use of LPG is Rp.761. Based on this value, a comparison of 234.461235% found that gas fuel is more efficient than oil fuel. The average pertalite consumption cost at moderate RPM is Rp.2,926.125, while for LPG use it is Rp.1,115. Based on the value found a comparison of 262.432735% gas fuel is more efficient than fuel oil. The average pertalite consumption at high RPM is Rp.4,271.25, while the use of LPG is Rp.1,574. Based on the average value of fuel consumption at high RPM, a comparison of 271.36277 was found. Gas fuel is more economical than the use of fuel oil in the katinting engine, seen from the comparison of the percentage of the consumption of fuel oil and gas fuel at each RPM.